Speech perception as an active cognitive process - Heald, Shannon; Nusbaum, Howard C. (Frontiers in Systems Neuroscience, 2014)
One view of speech perception is that acoustic signals are transformed into representations for pattern matching to determine linguistic structure. This process can be taken as a statistical pattern-matching problem, assuming realtively stable linguistic categories are characterized by neural representations related to auditory properties of speech that can be compared to speech input. This kind of pattern matching can be termed a passive process which implies rigidity of processingd with few demands on cognitive processing. An alternative view is that speech recognition, even in early stages, is an active process in which speech analysis is attentionally guided. Note that this does not mean consciously guided but that information-contingent changes in early auditory encoding can occur as a function of context and experience. Active processing assumes that attention, plasticity, and listening goals are important in considering how listeners cope with adverse circumstances that impair hearing by masking noise in the environment or hearing loss. Although theories of speech perception have begun to incorporate some active processing, they seldom treat early speech encoding as plastic and attentionally guided. Recent research has suggested that speech perception is the product of both feedforward and feedback interactions between a number of brain regions that include descending projections perhaps as far downstream as the cochlea. It is important to understand how the ambiguity of the speech signal and constraints of context dynamically determine cognitive resources recruited during perception including focused attention, learning, and working memory. Theories of speech perception need to go beyond the current corticocentric approach in order to account for the intrinsic dynamics of the auditory encoding of speech. In doing so, this may provide new insights into ways in which hearing disorders and loss may be treated either through augementation or therapy.